ANALISIS KEPUASAN MASYARAKAT JENANGAN TERHADAP KEBIJAKAN SUBSIDI LISTRIK DI MASA PANDEMI - Amanda Kamaliyah Rosyadah; Alfania Yulantias; Augustin Rina Herawati; Kismartini . (Fakultas Politik Pemerintahan IPDN, 2022)
Abstract The electricity subsidy policy that was born during the COVID-19 pandemic in several regions in Indonesia has been less effective and has caused some people's dissatisfaction. Jenangan District, Ponorogo Regency is one of the areas that receives electricity subsidies, especially for 450 VA and 900 VA customers. The problem is focused on the level of community satisfaction on the electricity subsidy policy during the pandemic which was less effective because it was not on target. The purpose of the study was to determine the community's satisfaction with the electricity subsidy program. This study uses qualitative methods through interviews and questionnaires to 30 sources. Community satisfaction was measured using a Likert scale and analyzed descriptively. The results showed that for 450 VA users during April, May, and June 2020 54.5% of respondents did not get electricity subsidies and for 900 VA users during those three months 81.3% of respondents did not get a 50% discount for electricity payments. This is what causes the Jenangan people in Ponorogo Regency to be dissatisfied with the electricity subsidy policy during the pandemic which is shown through with the results of 40% of respondents saying they are not satisfied, 20% are very satisfied, 20% are satisfied, 16.7% are quite satisfied, and the remaining 3.3% said they were not satisfied. Keywords: Electricity Subsidy Policy, Public, Government, and Public Satisfaction.